Intranasal Fentanyl to Reduce Pain and Improve Oral Intake in the Management of Children With Painful Infectious Mouth Lesions. Issue 8 (5th August 2022) - Ruffin, Thomas B.; Salinero, Efren; Papa, Linda; Cramm, Kelly; Florez, Camilo; Chen, J. Gene; Ramirez, Jose
Abstract : Objectives: Painful infectious mouth conditions such as herpangina, hand-foot-and-mouth disease, and herpetic gingivostomatitis can cause pain, dehydration, and hospitalization in young children. Treatment for these conditions is generally supportive and directed toward pain relief from ulcerative lesions, thus facilitating oral intake, and preventing dehydration. Attempts at oral therapy at home and in the emergency department are often refused and immediately spit back out. This study evaluated the efficacy of intranasal fentanyl (INF) compared with a commonly used oral (PO) acetaminophen/hydrocodone formulation for the treatment of children with painful infectious mouth conditions. Methods: This study was a prospective, nonblinded, randomized controlled noninferiority trial conducted in an academic tertiary care pediatric emergency department. The study enrolled children between the ages of 6 months and 18 years with painful infectious mouth lesions and poor oral intake. Patients were randomized to receive either INF (1.5 μg/kg, intervention) or PO acetaminophen/hydrocodone (0.15 mg/kg, control) based on the dose of hydrocodone. The primary outcome was volume of fluid intake per body weight (in milliliters per kilogram) 60 minutes after analgesic administration. Secondary outcomes included pain scores using a validated visual assessment scale (VAS; 1, no pain; 10, worst pain), hydration score (VAS; 1, well hydrated; 4, very dehydrated), admission rate and overall satisfaction score (VAS; 1, worst; 7, best). A priori power analysis indicated that 34 patients would achieve an 81% power with an α value of 0.05. Results: Of the 34 patients enrolled, 17 were randomized to INF and 17 to PO. The demographics between both groups were similar in age, weight, sex, and race. There were no significant differences in parental perception of pain ( P = 0.69) or hydration status ( P = 0.78). Oral fluid intake at 60 minutes was 20 mL/kg for INF versus 18 mL/kg for PO ( P = 0.53). Pain scores at 15 and 30 minutes were 1.7 versus 2.9 ( P = 0.09) and 0.6 versus 1.6 ( P = 0.59). Parental perceptions of pain and hydration status at 60 minutes were 2.2 versus 2.4 ( P = 0.77) and 1.7 versus 1.5 ( P = 0.37). Overall parental satisfaction was 6.4 for INF versus 6.5 for PO ( P = 0.71), and admission rate was 0 vs 12% ( P = 0.49). There were no adverse events such as respiratory, cardiac, or central nervous system depression in either group. Conclusions: Intranasal fentanyl seems to be a safe and effective alternative to acetaminophen with hydrocodone in reducing pain and improving hydration status in children with painful infectious mouth lesions and poor oral intake.